β-Cell-Specific Mafk Overexpression Impairs Pancreatic Endocrine Cell Development. - Ahmed M Abdellatif; Hisashi Oishi; Takahiro Itagaki; Yunshin Jung; Hossam H Shawki; Yukari Okita; Yoshikazu Hasegawa; Hiroyuki Suzuki; Salah E El-Morsy; Mesbah A El-Sayed; Mahmoud B Shoaib; Fumihiro Sugiyama; et al. (PLoS ONE, 2016)
The MAF family transcription factors are homologs of v-Maf, the oncogenic component of the avian retrovirus AS42. They are subdivided into 2 groups, small and large MAF proteins, according to their structure, function, and molecular size. MAFK is a member of the small MAF family and acts as a dominant negative form of large MAFs. In previous research we generated transgenic mice that overexpress MAFK in order to suppress the function of large MAF proteins in pancreatic β-cells. These mice developed hyperglycemia in adulthood due to impairment of glucose-stimulated insulin secretion. The aim of the current study is to examine the effects of β-cell-specific Mafk overexpression in endocrine cell development. The developing islets of Mafk-transgenic embryos appeared to be disorganized with an inversion of total numbers of insulin+ and glucagon+ cells due to reduced β-cell proliferation. Gene expression analysis by quantitative RT-PCR revealed decreased levels of β-cell-related genes whose expressions are known to be controlled by large MAF proteins. Additionally, these changes were accompanied with a significant increase in key β-cell transcription factors likely due to compensatory mechanisms that might have been activated in response to the β-cell loss. Finally, microarray comparison of gene expression profiles between wild-type and transgenic pancreata revealed alteration of some uncharacterized genes including Pcbd1, Fam132a, Cryba2, and Npy, which might play important roles during pancreatic endocrine development. Taken together, these results suggest that Mafk overexpression impairs endocrine development through a regulation of numerous β-cell-related genes. The microarray analysis provided a unique data set of differentially expressed genes that might contribute to a better understanding of the molecular basis that governs the development and function of endocrine pancreas.